Comunicação para alteridade: expedições fotográficas como exercício da pedagogia da intersubjetividade - Dabdab, Roberta (2022)
The present work is the result of two “anthropo-socioecological” experiments with teenagers from the Heliópolis favela, structured from the challenge of thinking about educational approaches and/or competent public policies to bring together different contexts. Understanding that the reality “of the other” must be experienced, we adopted photographic expeditions and the photographic gesture as mobilizing agents for the encounter with “the others” and involvement with the environment, in addition to enabling the regression of the dimensional losses of the body in the established relationships with the world of life. We also believe the tours and encounters provided by the expeditions as a “gap” for the activation of bodies, senses, imagination and the recognition of the other, therefore, of the self. In this sense, the pedagogy of intersubjectivity proposed by Vilém Flusser in “Brazilian environment”, which is also contextualized in this work, offers us a robust foundation for the “design” of our practice. The Flusserian perspective follows the ecological paradigm, is critical of humanism and articulates with the ontological turn of the disciplines that start to consider the environment as the background of the relationships that make up reality. In this sense, his communicology begins with the non-separation between subject and object, culture and nature, or any other dualism, and dialogues directly with Oswald de Andrade's anthropophagy and Husserl's phenomenology. The methodology is based on Harry Pross' Media Theory and his considerations about the "primary media" and will follow the paths pointed out by Vilém Flusser (Intersubjectivity), Dietmar Kamper (KörperDenken), Norval Baitello (Iconophagy and Sitting Thinking) and Paulo Freire (Conscientization). We defend the pedagogy of intersubjectivity as a precursory and urgent approach to our communication and education in a technological context, a context that challenges us to think of ways to “pierce” social and communicational bubbles